Resource intensive production and aggregate economic performance - Ian Keay (Queen's University, Department of Economics, 2008)
The main objective of this paper is to determine whether specialization in resource intensive production had a positive impact on the performance of the aggregate Canadian economy over the 1970-2005 period. Specialization is simply measured as the proportion of aggregate employment, the aggregate fixed capital stock, and G.N.P. that may be attributed to Canada's energy, fishing, forestry, and mining industries. Direct contributions to intensive, or per capita performance are measured in terms of the resource industries' profitability, productivity, and capital intensity. Indirect contributions to economic performance are measured in terms of spill overs, or linkages to other non-resource intensive industries through raw material price advantages and demand generation. The possibility that resource intensive production may have been crowding out other sectors in the economy through input price inflation or currency appreciation is also investigated. Based on the evidence, I argue that Canada's resource industries were making a substantial positive impact on aggregate economic performance after 1970, but this conclusion depends on the inclusion of the energy industries in resource sector.
Keywords: N52; O13; 330; Resource Dependence; Spill Overs; Crowding Out; Resource Based Growth; Gesamtwirtschaftliche Produktion; Rohstoffressourcen; Arbeitsteilung; Energieressourcen; Fischerei; Forstwirtschaft; Bergbau; Spillover-Effekt; Kanada